The Petri Dish-N2B27 Culture Condition Maintains RPE Phenotype by Inhibiting Cell Proliferation and mTOR Activation - Hui Lou; Chunpin Lian; Fanjun Shi; Liqun Chen; Sicheng Qian; Hui Wang; Xiaoyun Zhao; Xiaoyan Ji; Jingfa Zhang; Guoxu Xu (Journal of Ophthalmology)
Objective. To develop a method for the rapid isolation of rat RPE cells with high yield and maintain its epithelial state in modified culture system. Methods. The eyeballs were incubated with dispase. The retina was isolated with RPE attached and cut into several pieces. Following a brief incubation in growth medium, large RPE sheets can be harvested rapidly. RPE cells were divided into four groups and cultured for several weeks, that is, (1) in cell culture dishes with 10% FBS containing medium (CC dish-FBS), (2) in petri dishes with 10% FBS containing medium (Petri dish-FBS), (3) in cell culture dishes with N2 and B27 containing medium (CC dish-N2B27), and (4) in petri dishes with N2 and B27 containing medium (Petri dish-N2B27). Morphological and biological characteristics were investigated using light microscopy, Q-PCR, and western blot. Results. The retina would curl inwardly during the growth medium incubation period, releasing RPE sheets in the medium. Compared with low density group (5,000 cells/cm2), RPE cells plated at high density (15,000 cells/cm2) can maintain RPE morphology for a more extended period. Meanwhile, plating RPE cells at low density significantly reduced the expression of RPE cell type-specific genes (RPE65, CRALBP, and bestrophin) and increased the expression of EMT-related genes (N-cadherin, fibronectin, and α-SMA), in comparison with the samples from the high density group. The petri dish culture condition reduced cell adhesion and thus inhibited RPE cell proliferation. As compared with other culture conditions, RPE cells in the petri dish-N2B27 condition could maintain RPE phenotype with increased expression of RPE-specific genes and decreased expression of EMT-related genes. The AKT/mTOR pathway was also decreased in petri dish-N2B27 condition. Conclusion. The current study provided an alternative method for easy isolation of RPE cells with high yield and maintenance of its epithelial morphology in the petri dish-N2B27 condition.